First record of the genus Myllaena Erichson from Brazil, description of a new species and annotated catalog of Myllaena species from the Neotropical region (Coleoptera, Staphylinidae, Aleocharinae) - Caron,Edilson (2008)
The genus Myllaena Erichson, 1837, of the tribe Myllaenini Ganglbauer, 1895, is recorded from Brazil for the first time. A new species, Myllaena brasiliensis sp. nov., is described and illustrated; it is closely related to the insomnis species group, described from the Nearctic region. A short diagnosis of the genus and an annotated catalog of Myllaena species from the Neotropical region are also provided.